Macroeconomics principles, problems and policies / Campbell R. McConnell; Stanley L. Brue - McConnell, Campbell R.; Brue, Stanley L. (1996)
An introduction to economics and the economy, the nature and method of economics, the economizing problem, understanding individual markets: demand and supply, pure capitalism and the market system, the mixed economy: private and public sectors, the united states in the global economy; national income, employment and fiscal policy, measuring domestic output, national income, and the price level, macroeconomic instability: unemployment and inflation, building the aggregate expenditures model, aggregate expenditures: the multiplier, net exports, and government, aggregate demand and aggregate supply, fiscal policy; money, banking, and monetary policy, money and banking, how banks create money, the federal reserve banks and monetary, policy; problems and controversies in macroeconomics, alternative views on macro theory and policy, the inflation unemployment relationship, budget deficits and the public debt, economic growth; international economics and the world economy, international trade, exchange rates, the balance of payments, and trade deficits, growth and the less developed countries, Russia: an economy in transition